Murdoch mysteries. Season 17 [videorecording (DVD)] - Bisson, Yannick, 1969-; Joy, Hélène; Craig, Tom, 1962-; Harris, Jonny; Maslany, Daniel, 1988-; Murdoch, Lachlan, 1986-; Keleghan, Peter, 1959-; Humphreys, Arwen; Banton, Shanice; McConnell, Clare; Santos, Bienvenido N.; Walkes, Samantha; et al. (Acorn, 2024)
Murdoch and his wife have been abducted and Inspector Brackenreid has retired, leaving only Constable Crabree to investigate the corruption inside the station house. As the team reassembles, their new cases involve Sun Yat-Sen, Jelly Roll Morton, the Scottish Highland games, and leave Murdoch in a coma after a shooting, dreaming of a world where mysteries are investigated musically.